Qubit Mapping for Reconfigurable Atom Arrays - Tan, Bochen; Bluvstein, Dolev; Lukin, Mikhail D.; Cong, Jason (2022 IEEE/ACM International Conference On Computer Aided Design (ICCAD), 2022)
Because of the largest number of qubits available, and the massive parallel execution of entangling two-qubit gates, atom arrays is a promising platform for quantum computing. The qubits are selectively loaded into arrays of optical traps, some of which can be moved during the computation itself. By adjusting the locations of the traps and shining a specific global laser, different pairs of qubits, even those initially far away, can be entangled at different stages of the quantum program execution. In comparison, previous QC architectures only generate entanglement on a fixed set of quantum register pairs. Thus, reconfigurable atom arrays (RAA) present a new challenge for QC compilation, especially the qubit mapping/layout synthesis stage which decides the qubit placement and gate scheduling. In this paper, we consider an RAA QC architecture that contains multiple arrays, supports 2D array movements, represents cutting-edge experimental platforms, and is much more general than previous works. We start by systematically examining the fundamental constraints on RAA imposed by physics. Built upon this understanding, we discretize the state space of the architecture, and we formulate layout synthesis for such an architecture to a satisfactory modulo theories problem. Finally, we demonstrate our work by compiling the quantum approximate optimization algorithm (QAOA), one of the promising near-term quantum computing applications. Our layout synthesizer reduces the number of required native two-qubit gates in 22-qubit QAOA by 5.72x (geomean) compared to leading experiments on a superconducting architecture. Combined with a better coherence time, there is an order-of-magnitude increase in circuit fidelity.